2022
DOI: 10.3389/fimmu.2022.1096009
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of a glycolysis and cholesterol synthesis-related genes signature for predicting prognosis and immune landscape in osteosarcoma

Abstract: BackgroundGlycolysis and cholesterol synthesis are crucial in cancer metabolic reprogramming. The aim of this study was to identify a glycolysis and cholesterol synthesis-related genes (GCSRGs) signature for effective prognostic assessments of osteosarcoma patients.MethodsGene expression data and clinical information were obtained from GSE21257 and TARGET-OS datasets. Consistent clustering method was used to identify the GCSRGs-related subtypes. Univariate Cox regression and LASSO Cox regression analyses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…However, because of gene naming alterations and gene absences in microarray datasets, only 53 published signatures and the AIDPI were tested in at least one cohort, and the results were visualized in a heat map (Figure 1N). Strikingly, this heat map showed that only two signatures consistently exhibited statistical significance across all cohorts: our AIDPI and Xu et al.’s signature 12 . A direct C‐index comparison underscored AIDPI's definitive superiority over Xu et al.’s signature within three cohorts (Figure 1O).…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…However, because of gene naming alterations and gene absences in microarray datasets, only 53 published signatures and the AIDPI were tested in at least one cohort, and the results were visualized in a heat map (Figure 1N). Strikingly, this heat map showed that only two signatures consistently exhibited statistical significance across all cohorts: our AIDPI and Xu et al.’s signature 12 . A direct C‐index comparison underscored AIDPI's definitive superiority over Xu et al.’s signature within three cohorts (Figure 1O).…”
Section: Resultsmentioning
confidence: 81%
“…Strikingly, this heat map showed that only two signatures consistently exhibited statistical significance across all cohorts: our AIDPI and Xu et al.’s signature. 12 A direct C‐index comparison underscored AIDPI's definitive superiority over Xu et al.’s signature within three cohorts (Figure 1O ). These findings demonstrate that the AIDPI can predict OSA patients’ outcomes and outperforms previously established signatures.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Hypercholesterolemia facilitated the entry of Chol into cancer cells [ 10 ] due to the overexpression of the LDL receptor in these cells [ 11 ]. Moreover, metabolic reprogramming in transformed cells was described [ 12 ]. Thus, the upregulation of enzymes for Chol synthesis was demonstrated in cancer cells [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%